PENGARUH WORD OF MOUTH, KUALITAS MAKANAN DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ANGKRINGAN DISINIAJA KARANGANYAR: PENGARUH WORD OF MOUTH, KUALITAS MAKANAN DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ANGKRINGAN DISINIAJA KARANGANYAR - alviana eka kimilawati; Rahayu Triastity; Sumaryanto Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2022)
The purpose of this study was to analyze the significance of the influence of word of mouth, food quality and store atmosphere on consumer purchasing decisions at Angkringan siniaja Karanganyar. This research is a survey research. The research population of consumers Angkringan Disiniaja Karanganyar. The sample is 100 people with accidental sampling technique. Data collection techniques used questionnaires and literature study. The data analysis technique used multiple linear regression analysis. The results showed that word of mouth, food quality and store atmosphere had a significant effect on consumer purchasing decisions at Angkringan Diiniaja Karanganyar.